Epithelial Haven and Autophagy Breakout in Gonococci Infection - Mendes, Ana Clara; Ciccone, Marcone; Gazolla, Bruna; Bahia, Diana (Frontiers in Cell and Developmental Biology, 2020)
The World Health Organization (WHO) has estimated that in 2016, there were 87 million new cases of gonorrhoea. Gonorrhoea is caused by the sexually transmitted human-exclusive agent Neisseria gonorrhoeae, a Gram-negative diplococcus that causes cervicitis in females and urethritis in males and may lead to more severe complications. Currently, there is no vaccine against N. gonorrhoeae. Its resistance to antibiotics has been increasing in the past few years, reducing the range of treatment options. N. gonorrhoeae requires a surface protein/receptor (Opa proteins, porin, Type IV pili, LOS) to adhere to and invade epithelial cells. During invasion and transcytosis, N. gonorrhoeae is targeted by the autophagy pathway, a cellular maintenance process which balances sources of energy at critical times by degrading damaged organelles and macromolecules in the lysosome. Autophagy is an important host defense mechanism which targets invading pathogens. Based on Transmission Electron Microscopy (TEM) analysis, the intracellular bacteria occupy the autophagosome, a double-membraned vesicle that is formed around molecules or microorganisms during macroautophagy and fuses with lysosomes for degradation. Most of the gonococci end up in autolysosomes for degradation, but a subpopulation of the intracellular bacteria inhibits the maturation of the autophagosome and its fusion with lysosomes by activating mTORC1 (a known suppressor of the autophagy signaling), thus escaping autophagic elimination. This mini review focuses on the cellular features of N. gonorrhoeae during epithelial cell invasion, with a particular focus on how N. gonorrhoeae evades the autophagy pathway.